ТАХТАКӨПИР РАЙОНЫ ТОПОНИМЛЕРИНИҢ ПАЙДА БОЛЫЎ СЕБЕПЛЕРИ ҲАҚҚЫНДА - Серикбаева, А.С. (SCIENCE and SOCIETY, 2021)
Each toponym, hydronym, oronym has a secret and history of naming. The article discusses the origin of naming some toponyms of Takhtakopir region,which full of rich toponymic information.
Keywords: onomastics; toponym; oikonym; oronym; hydronym; anthroponym; ethnonym